Manajemen Kegiatan Ekstrakurikuler di SD Al Irsyad 01 Purwokerto - Slamet Nuryanto (Institut Agama Islam Negeri Purwokerto, 2017)
The study was aimed at describing the management function of extracurricular activities in Al Irsyad 01 Elementary School of Purwokerto along with supporting and inhibiting factors in the implementation of such activities. This is a qualitative descriptive research with case study as research approach. Data collection is done by in-depth interview, documentation, and participant observation. To maintain the validity of the data, this study uses extension opt-in techniques, observational persistence and triangulation. The findings of this study indicate the existence of an extracurricular activity program conducted by the school for one academic year, the existence of organizational structure on each type of extracurricular activities, including the process of planning, implemention, and evaluation of extracurricular activities.